The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00466-008-0285-z
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of composite and sandwich plates using an improved discrete Kirchhoff quadrilateral element based on third-order zigzag theory

Abstract: The new improved discrete Kirchhoff quadrilateral element based on the third-order zigzag theory developed earlier by the present authors for the static analysis of composite and sandwich plates is extended for dynamics and assessed for its performance for the free vibration response. The element is free from the shear locking. The finite element formulation is validated by comparing the results for simply supported plates with the analytical Navier solution of the zigzag theory. Comparison of the present resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(70 citation statements)
references
References 48 publications
8
62
0
Order By: Relevance
“…These functions satisfy the clamped boundary conditions at 1 0 = x , that is where the same Gram-Schmidt approximation scheme is used as in the previous example (Problem 2.) In addition, a high-fidelity FEA is performed [43] and its results are used as reference solutions.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…These functions satisfy the clamped boundary conditions at 1 0 = x , that is where the same Gram-Schmidt approximation scheme is used as in the previous example (Problem 2.) In addition, a high-fidelity FEA is performed [43] and its results are used as reference solutions.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The six-node plate element developed is a nonconforming element as the element does not satisfy the normal slope continuity requirement. Thus, Kulkarni and Kapuria [34] indicated that the six-node triangular element [33] underestimated the natural frequencies of the sandwich plates. Therefore, three-node triangular element based on the C 1 -type zig-zag model [18] has been developed for comparison in this paper.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…In Table 8, the first ten circular frequencies, computed with different approaches, are compared with the RZT results. Solution cited as 3D FE [58] is obtained by means of three-dimensional finite element analysis and it can be considered as a reference result. For comparison purposes, solutions are also obtained with FSDT (shear correction factors as in [55]).…”
Section: A/2hmentioning
confidence: 99%